2010
DOI: 10.1021/ja103016y
|View full text |Cite
|
Sign up to set email alerts
|

A Metal−Organic Framework with Covalently Bound Organometallic Complexes

Abstract: A procedure for making covalently linked organometallic complexes within the pores of metal-organic frameworks (MOFs) has been described. An N-heterocyclic carbene precursor containing link L0 was prepared and then constructed into a MOF-5-type structure (IRMOF-76). Attempts to produce covalently bound organometallic complexes in IRMOF-76 were unsuccessful. An alternative way of linking the first metalated link, L1, into the desired metalated MOF structure, IRMOF-77, was successful. IRMOF-76 and -77 were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
137
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 36 publications
0
137
0
1
Order By: Relevance
“…16 However, also the incorporation of NHCs into a polymer backbone has been reported to increase their stability. 17 Recent studies showed that functionalized NHCs can also be applied as maintaining part of metal organic frameworks (MOFs) 18 or in polymer networks with intrinsic microporosity (PIMs). 19,20 The latter materials are prepared from rigid and contorted molecules, oen called knots or tectons which are polymerized either directly or using linear linkers.…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%
“…16 However, also the incorporation of NHCs into a polymer backbone has been reported to increase their stability. 17 Recent studies showed that functionalized NHCs can also be applied as maintaining part of metal organic frameworks (MOFs) 18 or in polymer networks with intrinsic microporosity (PIMs). 19,20 The latter materials are prepared from rigid and contorted molecules, oen called knots or tectons which are polymerized either directly or using linear linkers.…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%
“…9 Alternatively, Yaghi and co-workers have shown that pre- 40 formed NHC complexes can be utilized as framework links. 10 Furthermore, NHC complex generation concomitant with MOF synthesis has been reported. 11 In these examples the NHC complex is appended to the framework and protrudes into the available pore space.…”
mentioning
confidence: 99%
“…Recent examples of azolium containing ligands have all been based on an imidazolium [9,10] or a benzimidazolium [11] precursor to the N-heterocyclic carbene. The imidazolium containing ligands for MOF synthesis have come in two forms; the first where the azolium is integrated into the backbone of the ligand, [9] and the second, where the azolium moiety is incorporated pendant to the link.…”
Section: Introductionmentioning
confidence: 99%
“…[9a-c] We, [9d] Chun et al, [9e, 9f] and Hupp [9g] have also reported frameworks based on more rigid linkers where an imidazolium is part of the link (3 -6), which confers an unusual zeolite-like geometry on the link component in these structures. Finally, Yaghi [11] reported a system partway between these extremes by using a benzimidazolium core to generate a linear dicarboxylate (7) whereby the azolium was integrated into the link backbone of a cubic MOF. More recently a linker with two azolium groups in the backbone (8) was used to synthesis a 2-D MOF network consisting of 80-membered macrocycle rings of 8 bridging copper paddle-wheel subunits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation